Visible light-induced synthesis of polysulfone-based graft copolymers by a grafting from approach - Çiftçi, Mustafa; Tasdelen, Mehmet Atilla (Wiley, 2020)
The synthesis of polysulfone (PSU) graft copolymers by a two-step "grafting from" approach is described. First, a chlorofunctional PSU (PSU-Cl) is formed via chloromethylation of a commercial PSU. The formed polymers are used macroinitiator for the dimanganese decacarbonyl assisted free-radical polymerization of tert-butyl acrylate, methyl methacrylate, and styrene to give the desired graft copolymers. Moreover, amphiphilic graft copolymers are also formed via posthydrolyzation of poly(tert-butyl acrylate) containing graft copolymers. The intermediates at various stages and the ultimate graft copolymers are characterized by various analysis techniques. (c) 2020 Wiley Periodicals, Inc. J. Polym. Sci. 2020, 58, 412-416
Keywords: graft copolymers; photopolymerization; grafting from; polysulfones; visible light